A New Practical Decision Rule to Better Differentiate BI‐RADS 3 or 4 Breast Masses on Breast Ultrasound. (4th May 2021) - Pfob, André; Barr, Richard G.; Duda, Volker; Büsch, Christopher; Bruckner, Thomas; Spratte, Julia; Nees, Juliane; Togawa, Riku; Ho, Chi; Fastner, Sarah; Riedel, Fabian; Schaefgen, Benedikt; et al.
Abstract : Objectives: The BI‐RADS classification provides a standardized way to describe ultrasound findings in breast cancer diagnostics. However, there is little information regarding which BI‐RADS descriptors are most strongly associated with malignancy, to better distinguish BI‐RADS 3 (follow‐up imaging) and 4 (diagnostic biopsy) breast masses. Methods: Patients were recruited as part of an international, multicenter trial (NCT02638935). The trial enrolled 1294 women (6 excluded) categorized as BI‐RADS 3 or 4 upon routine B‐mode ultrasound examination. Ultrasound images were evaluated by three expert physicians according to BI‐RADS. All patients underwent histopathological confirmation (reference standard). We performed univariate and multivariate analyses (chi‐square test, logistic regression, and Krippendorff's alpha). Results: Histopathologic evaluation showed malignancy in 368 of 1288 masses (28.6%). Upon performing multivariate analysis, the following descriptors were significantly associated with malignancy ( P < .05): age ≥50 years (OR 8.99), non‐circumscribed indistinct (OR 4.05) and microlobulated margin (OR 2.95), nonparallel orientation (OR 2.69), and calcification (OR 2.64). A clinical decision rule informed by these results demonstrated a 97% sensitivity and missed fewer cancers compared to three physician experts (range of sensitivity 79–95%) and a previous decision rule (sensitivity 59%). Specificity was 44% versus 22–83%, respectively. The inter‐reader reliability of the BI‐RADS descriptors and of the final BI‐RADS score was fair‐moderate. Conclusions: A patient should undergo a diagnostic biopsy (BI‐RADS 4) instead of follow‐up imaging (BI‐RADS 3) if the patient is 50 years or older or exhibits at least one of the following features: calcification, nonparallel orientation of mass, non‐circumscribed margin, or posterior shadowing. Abstract : Access the CME test here and search by article title.